2007
DOI: 10.1038/emm.2007.40
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1A1 (CYP1A1) polymorphisms and breast cancer risk in Korean women

Abstract: Cytochrome P450 1A1 (CYP1A1) is involved in the 2-hydroxylation of estrogen, the hormone that plays a critical role in the etiology of breast carcinoma. We evaluated the associations between two CYP1A1 polymorphisms [MspI (rs4646903); Ile462Val (rs1048943)] and breast cancer in a multicenter case-control study of 513 breast cancer cases and 447 controls in Korea. Women carrying the T allele of the CYP1A1 MspI polymorphism were found to have a 1.72-fold (95% CI 1.11-2.68) greater risk of developing breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 19 publications
4
25
0
1
Order By: Relevance
“…Examining genotype frequencies in controls, significant deviation from HWE was detected in four studies, i.e., the Caucasian part of the study by Bailey et al [41], the Caucasian part of the study by Taioli et al [29], the study by Chacko et al [51] and Shin et al [63]. After the exclusion of the four studies significantly departing from HWE the results remained practically unchanged.…”
Section: T3801c Polymorphismmentioning
confidence: 87%
See 1 more Smart Citation
“…Examining genotype frequencies in controls, significant deviation from HWE was detected in four studies, i.e., the Caucasian part of the study by Bailey et al [41], the Caucasian part of the study by Taioli et al [29], the study by Chacko et al [51] and Shin et al [63]. After the exclusion of the four studies significantly departing from HWE the results remained practically unchanged.…”
Section: T3801c Polymorphismmentioning
confidence: 87%
“…Concerning T3801C polymorphism, 32 studies were eligible (11,909 [28,31,33,50,54,62,63,66]; and three studies on African subjects (356 cases and 459 controls) [29,34,41].…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Results of association studies for this SNP are similar to other two SNPs and controversial as well. Associations of this polymorphism was proved in African-American population (Taioli et al, 1995), and also in Korean and Chinese populations (Shen et al, 2006;Shin et al, 2007), but Kiruthiga et al (2011) found no specific association of this polymorphism with breast cancer in Indian women.…”
Section: Discussionmentioning
confidence: 99%
“…Results of investigations performed in different populations showed controversial results. For example, it was shown that the genotype of clinical significance for Chinese women is CC [10], whereas for Korean women T allele was shown to be a risk associated [11] and for the women of North America [12] the correlations of polymorphism in this site with BC were not evaluated.…”
Section: Resultsmentioning
confidence: 99%